Hearing on the National Commission on Libraries and Information Science (NCLIS). Hearing before the Subcommittee on Postsecondary Education of the Committee on Education and Labor. House of Representatives, Ninety-Seventh Congress, Second Session - Congress of the U.S., Washington, DC. House Committee on Education and Labor; Congress of the U.S., Washington, DC. House Committee on Education and Labor ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This hearing contains testimony presented at a hearing conducted to investigate the legality of the President's early termination of the appointments of three members of the National Commission on Libraries and Information Science (NCLIS). On September 21, 1981, three NCLIS commissioners, Clara Jones, Frances Naftalin, and Joan Gross, received notices from the White House that their 5-year commission appointments, due to expire in July 1982, were being terminated immediately. This action was considered to be of questionable constitutionality, since while the commissioners are appointed by the President, the length of the terms they are to serve is mandated by the law that established the commission. At the conclusion of the hearing, Chairman Simon stated that, as an initial step, he would write to the Justice Department. If this action did not settle the matter, he suggested that the subcommittee had basically two options; either a resolution by the House, or a temporary injunction against the removal of the commissioners from NCLIS. This document includes the opening statement of the Hon. Paul Simon, chairman of the subcommittee, and the statements of Frederick Burkhardt, chairman emeritus of NCLIS, and Clara Jones and Frances Naftalin. (DMC)
Educational level discussed: Postsecondary Education.
Policymakers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Constitutional Law; Federal Legislation; Federal Regulation; Government Role; Hearings; Information Science; Libraries; Postsecondary Education; Public Policy; National Commission Libraries Information Science; Congress 97th; Legal/Legislative/Regulatory Materials